Perceived Decrease in Workplace Security Since the Beginning of the COVID-19 Pandemic: The Importance of Management Styles and Work-Related Attitudes - Wojtkowska, Anna; Tyburski, Ernest; Skalacka, Katarzyna; Gasiorowska, Agata (Frontiers in Psychology, 2021)
COVID-19 pandemic has reduced people’s sense of security in everyday life. However, managers’ efforts in the workplace to minimize health risks and economic damage can provide employees with a greater sense of security The aim of this study was to analyze potential drop in subjective sense of security in the workplace before the pandemic and during first two weeks after European outbreak, and relations between this drop and demographics and psychological factors. Three hundred thirty-seven Polish employees aged 18–61 were surveyed using an on-line form during first two weeks of COVID-19 pandemic. Using cluster analysis, we identified four subgroups of employees, differing in their sense of workplace security, work-related psychological factors and perceived management styles of their supervisors. The most beneficial appear to be those employees leaded by developer and executive managers, which kept high security sense and positive attitude to work. In worst situation seems to be employees leaded by compromiser and deserter managers – they suffer of highest drop of security. Interesting positive difference in security sense was observed among workers of autocratic leaders, which can improve subjective security during crisis but linked to lowest work satisfaction and greatest need to change the work. This paper proposes how employers can protect their employees from over-reactions and unnecessarily panic using soft, psychological competences.